Implementation of Guided Inquiry Learning Model on Colloid Systems to Improve Critical Thinking Ability of Students - Nurul R. Arini; Sri M. Sabang; Anang W. M. Diah (Jurnal Akademika Kimia, 2021)
Critical thinking is the ability to solve problems through an investigation so as to produce conclusions or rational decisions. This study aimed to obtain an improvement of critical thinking skills of students in Grade XI at SMAN 3 Palu after the implementation of the guided inquiry learning model on Colloid Systems. This study was a pre-experiment with one group pretest-posttest design. The sample was run by simple random sampling with the sample of Class XI Science 1 as the replication class 1 (n = 36) and Class XI Science 3 as the replication class 2 (n = 35). Data on students' critical thinking was taken using tests that were given before and after learning. An improvement in students' critical thinking skills in replication class 1 and replication class 2 was by 50%. Data of students' critical thinking skills were tested using non-parametric statistical analysis, namely the Mann-Whitney test. The test results obtained the Zh value -0.076, so -1.96 ≤ -0.076 ≤ +1.96. This result is in the reception area of Ho, and H1 is rejected. It means that the average score of critical thinking ability of students in the replication class 1 is the same as in replication class 2. This study concluded that the implementation of the guided inquiry learning model on Colloid Systems improves the critical thinking skills of students in Grade XI at SMAN 3 Palu.